Cross-Generational Differences in Independence and Interdependence: Discrepancies Between Their Actual and Ideal Selves in the Japanese Cultural Context - Hashimoto, Hirofumi (Frontiers in Psychology, 2021)
The current study examined cross-generational differences in both independent and interdependent self-construal. Two studies using samples from across Japan that included a wide age range demonstrated that, with increasing age, Japanese respondents scored higher on independence, which was measured by a self-expression scale, and lower on interdependence, as measured by a rejection avoidance scale. Furthermore, these cross-over effects were not observed with regard to participants’ preferences (i.e., the ideal state of the self), but were only observed in their actual selves (i.e., the actual state of the self). These results suggest that Japanese, especially younger generations, show the dilemma that they cannot help but behave in an interdependent way whereas they are eager to be independent.